Utilizing the Lactate Dehydrogenase-to-Albumin Ratio for Survival Prediction in Patients with Bladder Cancer After Radical Cystectomy - Xu H; Lin T; Ai J; Zhang J; Zhang S; Li Y; Zheng X; Zhang P; Wei Q; Tan P; Yang L (Dove Medical Press, 2023)
Hang Xu,1,2,* Tianhai Lin,1,2,* Jianzhong Ai,1,2,* Jiapeng Zhang,1,2 Shiyu Zhang,1,2 Yifan Li,1,2 Xiaonan Zheng,1,2 Peng Zhang,1,2 Qiang Wei,1,2 Ping Tan,1,2 Lu Yang1,2 1Department of Urology, West China Hospital, Sichuan University, Sichuan, People's Republic of China; 2Institute of Urology, West China Hospital, Sichuan University, Sichuan, People's Republic of China*These authors contributed equally to this workCorrespondence: Ping Tan; Lu Yang, Department of Urology, West China Hospital, Sichuan University, Sichuan, People's Republic of China, Tel +86 18980606829 ; +86 15208212056, Email uro_tanping@163.com; wycleflue@scu.edu.cnPurpose: Previous studies have suggested that the preoperative lactate dehydrogenase-to-albumin ratio (LAR) is correlated with survival in several cancers except bladder cancer (BCa). This study aimed to determine the prognostic value of the LAR in patients with urothelial carcinoma of the bladder (UCB) after radical cystectomy (RC).Patients and Methods: A total of 595 UCB patients with RC in West China Hospital from December 2010 to May 2020 were enrolled. A receiver operating characteristic (ROC) curve was used to determine the optimal cutoff value of the LAR. Kaplan-Meier curves and Cox regression analyses were applied to evaluate the association of the LAR with overall survival (OS) and recurrence-free survival. Independent factors in multivariate analyses were selected to construct nomograms. Calibration curves, ROC curves, concordance index (C-index) and decision curve analyses were used to evaluate the performance of the nomograms.Results: The optimal cutoff value of the LAR was determined to be 3.8. Preoperative low LAR was associated with decreased OS (P < 0.001) and RFS (P < 0.001), especially in patients with ≥ pT2 disease. LAR was an independent factor for OS (hazard ratio [HR]: 1.719; P < 0.001) and RFS (HR: 1.429; P = 0.012). The addition of the LAR into nomograms could result in better prediction performance. The areas under the curves of the nomograms were 0.821 and 0.801 for the prediction of 3-year OS and RFS, respectively. The C-indexes of the nomograms were 0.760 and 0.741 for the prediction of OS and RFS, respectively.Conclusion: The preoperative LAR is a novel and reliable independent prognostic biomarker for survival in UCB after RC.Keywords: lactate dehydrogenase, albumin, lactate dehydrogenase to albumin ratio, bladder cancer, prognosis